El Encuentro de las Tierras | The Confluence of Roots – a Video by D. Araúja, M. Zango, L. Pérez (Conference Modalities 2021, 2021)
El Encuentro de las Tierras | The Confluence of Roots – a Video Production by Diego Araúja, Matchume Zango and Lobadys Pérez (English subtitles) El Encuentro de las Tierras (The Confluence of Roots) is about relations, a poetics of relation, to use the words of the Caribbean intellectual, Edouard Glissant. In particular, it is about the contact between artistic and subjective roots. Possibly, it also connotes a confluence of languages and memories for the production of a relation between Brazil, Colombia and Mozambique. It is in this sense that the artists Diego Araúja (Brazil), Matchume Zango (Mozambique) and Lobadys Pérez (Colombia) make use of music, sound, choreography, documentary, literature and oral lyric to come up with a Creole and artistic production in this audiovisual work. El Encuentro de las Tierras (O Encontro das Terras) é sobre relação, uma poética da relação, como aponta o intelectual caribenho Edouard Glissant. Especialmente, sobre o contato entre terras artísticas, subjetivas. Possivelmente uma confluência de linguagens e memórias para a produção da relação entre Brasil, Colômbia e Moçambique. É neste sentido que os artistas Diego Araúja (Brasil), Matchume Zango (Moçambique) e Lobadys Pérez (Colômbia) se valem da música, do som, da coreografia, do documental, da literatura e da lírica oral para uma produção crioula e artística neste trabalho audiovisual. El Encuentro de las Tierras es sobre la relación, una poética de la relación, como señala el intelectual caribeño Edouard Glissant. Especialmente, sobre el contacto entre tierras artísticas, subjetivas. Posiblemente una confluencia de lenguajes y memorias para la producción de la relación entre Brasil, Colombia y Mozambique. Es en este sentido que los artistas Diego Araúja (Brasil), Matchume Zango (Mozambique) y Lobadys Pérez (Colombia) hacen uso de la música, el sonido, la coreografía, el documental, la literatura y la lírica oral para una producción criolla y artística en esta obra audiovisual. Direction & creation: Diego Araúja, Matchume Zango & Lobadys Pérez Original soundtrack (Ya Duma Ma Africa): Matchume Zango Choreography: Lobadys Pérez Script & text of narration: Diego Araúja Narration: Laís Machado Sound (Ya Duma Ma Africa): Fanuel Macuacua Sound effects and mixing (narration): Andrea Martins Singer: Bela Zango Dancers: Frey Gonzales, Mónica Laguna, Gina Collazos & Ingrid Londoño Special participation: D. Maria Celeste de Araújo Directors of photography: Diego Araúja, Nin La Croix, Matchume Zango & Lobadys Pérez Cameras: Diego Araúja, Nin La Croix, Ercilio Muchanga & Manuel Meléndez “Chino Slim” Assembly, editing & subtitling: Rana Tosto English translation: Raquel de Souza Spanish translation: Valerie V. V. Gruber & Carolina Beleño Garcia Executive production: Valerie V. V. Gruber, Gilbert Shang Ndi & Ute Fendler Artwork commissioned by the Africa Multiple Cluster of Excellence at the University of Bayreuth (Germany).